Activation of Peripheral T Follicular Helper Cells During Acute Dengue Virus Infection. (15th June 2018) - Haltaufderhyde, Kirk; Srikiatkhachorn, Anon; Green, Sharone; Macareo, Louis; Park, Sangshin; Kalayanarooj, Siripen; Rothman, Alan L; Mathew, Anuja
Abstract : We investigated the immune response of peripheral T follicular helper cells during acute dengue virus infection in Thai children. We report significant associations between peripheral T follicular helper cell activation and plasmablast activation, secondary infection, and disease. Abstract: Background: Follicular helper T cells (TFH ) are specialized CD4 T cells required for B-cell help and antibody production. Methods: Given the postulated role of immune activation in dengue disease, we measured the expansion and activation of TFH in the circulation (peripheral TFH [pTFH ]) collected from Thai children with laboratory-confirmed acute dengue virus (DENV) infection. Results: We found significant expansion and activation of pTFH subsets during acute infection with the highest frequencies of activated pTFH (PD1 hi pTFH and PD1 + CD38 + pTFH ) detected during the critical phase of illness. Numbers of activated pTFH were higher in patients with secondary compared with primary infections and in patients with more severe disease. We also found a positive correlation between the frequencies of activated pTFH and the frequencies of plasmablasts. Conclusions: To our knowledge, this is the first ex vivo analysis of pTFH activation during acute DENV infection. Overall, our study supports the model that pTFH contribute to disease evolution during the critical stage of illness.